Role of Sesamoid Bone in the Etiology of Trigger Finger in Hand - Ender Erden; Şule Şahin Onat; Emin Kürşad Uygunol (Türk Osteoporoz Dergisi, 2020)

(untitled)
Ultrasonography is the most important development that has been used in recent years during the diagnosis and treatment of musculoskeletal disorders. In this case report, the diagnosis process will be discussed due to ultrasonographic imaging of the sesamoid bone which is not seen in radiographic evaluation, which is the first step we used to image bone structure in a patient who diagnosed with trigger finger.